Pretransplant NPM1 MRD levels predict outcome after allogeneic hematopoietic stem cell transplantation in patients with acute myeloid leukemia - Kayser, Sabine; Stadtherr, Peter; Uppenkamp, Michael; Bochtler, Tilmann; Hegenbart, Ute; Ho, Anthony Dick; Dreger, Peter; Krämer, Alwin (Blood cancer journal, 2016)
The objective was to evaluate the prognostic impact of pre-transplant minimal residual disease (MRD) as determined by real-time quantitative polymerase chain reaction in 67 adult NPM1-mutated acute myeloid leukemia patients receiving allogeneic hematopoietic stem cell transplantation (HSCT). Twenty-eight of the 67 patients had a FLT3-ITD (42%). Median age at transplantation was 54.7 years, median follow-up for survival from time of allografting was 4.9 years. At transplantation, 31 patients were in first, 20 in second complete remission (CR) and 16 had refractory disease (RD). Pre-transplant NPM1 MRD levels were measured in 39 CR patients. Overall survival (OS) for patients transplanted in CR was significantly longer as compared to patients with RD (P=0.004), irrespective of whether the patients were transplanted in first or second CR (P=0.74). There was a highly significant difference in OS after allogeneic HSCT between pre-transplant MRD-positive and MRD-negative patients (estimated 5-year OS rates of 40 vs 89%; P=0.007). Multivariable analyses on time to relapse and OS revealed pre-transplant NPM1 MRD levels >1% as an independent prognostic factor for poor survival after allogeneic HSCT, whereas FLT3-ITD had no impact. Notably, outcome of patients with pre-transplant NPM1 MRD positivity >1% was as poor as that of patients transplanted with RD.
Gesehen am 11.02.2019